Answer:
(4) 29, 33, 37
(6) 53, 59, 65
(5) -16, -20, -24
Step-by-step explanation:
Simple Pythagorean theorem, And if you double check Tamara's work she is correct. Therefor B is the correct answer.
Answer:
Step-by-step explanation:
hello :
(2x + 9)(3-z) = 0 means : 2x+9=0 or 3-z=0
x= -9/2 or z=3
Answer:
Row 1 -
1/3, 1/2, 1/3, 2/3, 2/3, 8/15, 1/2.
Row 2 -
3/4, 3/4, 2/7, 21/25, 5/6, 7/9, 1/3.
Row 3 -
3/20, 7/20, 3/25, 3/5, 3/5, 1, 3/2 OR 1 1/2.
Hope this helped you out.
Answer:
6
Step-by-step explanation:
2 halves make a whole so multiply 2 by 3. the answer is six. you can also add the halves. 1/2+1/2+1/2+1/2+1/2+1/2=3.